2022
DOI: 10.1111/jocd.15022
|View full text |Cite
|
Sign up to set email alerts
|

Topical spray of Wharton's jelly mesenchymal stem cells derived from umbilical cord accelerates diabetic wound healing

Abstract: Background and Aim: Cell-based therapy utilizing mesenchymal stem cells (MSCs) is currently being investigated as a therapeutic agent for chronic wounds. There is no evidence regarding effectiveness of the spray and local transfer of this cellular product in diabetic wound healing. Accordingly, the present study, using clinical, pathological and biometric parameters, investigated the effectiveness of the spray of these cells in the healing of diabetic wounds in rats.Methods: Three days after the induction of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The change of c-peptide was significantly higher in the MSC-treated group than in the control group in adult-onset, but not different between groups among juvenile-onset T1DM [ 95 ]. Very recently, it has been shown that when a suspension spray including WJ-MSCs is applied on the wound area, it accelerates healing in diabetic wounds [ 96 ].…”
Section: Perinatal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of c-peptide was significantly higher in the MSC-treated group than in the control group in adult-onset, but not different between groups among juvenile-onset T1DM [ 95 ]. Very recently, it has been shown that when a suspension spray including WJ-MSCs is applied on the wound area, it accelerates healing in diabetic wounds [ 96 ].…”
Section: Perinatal Cellsmentioning
confidence: 99%
“…When two histone deacetylase (HDAC) inhibitors were tested, the pre-treatment with TMP269 improved the expression of insulin, somatostatin, GLUT2, PDX-1, PAX4, and NKX6.1 pancreatic markers [ 96 ]. Beikmohammadi et al [ 105 ] transfected WJ-MSCs in order to generate hepatocyte-like cells and differentiated them by using serial exposure to different inducing material and exogenous growth factors.…”
Section: Perinatal Cellsmentioning
confidence: 99%
“…In vivo-murine model [68] Wharton's jelly mesenchymal stem cells from umbilical cord Saline solution Syringe with spray head Diabetic wounds [105] has lower rejection and modulates the inflammatory phase response. The last-mentioned feature has been considered the main factor in reducing scar formation [134].…”
Section: Full-thickness Skin Excisionmentioning
confidence: 99%
“…13,14 WJMSCs suspension spray on the wound area can facilitate wound closure, promote the regeneration of epidermis and dermis, and increase skin elasticity. 15 However, subcutaneous injections will cause secondary damage to the skin tissue at the wound, which can easily lead to inflammation. Besides, diabetic wounds are further complicated because of reduced cytokine responses, infection, poor vascularization, and delayed healing processes.…”
Section: Introductionmentioning
confidence: 99%